Apple peel jejunal atresia: a case report - Dingore, Vaishnavi; Nage, Amol; Sheikh, Samir; Barot, Vaibhavi; Barot, Shailesh; Dixit, Prashant (International Journal of Contemporary Pediatrics, 2025)
Jejunal atresia type 3B (Apple peel variant) is a rare congenital anomaly of the small intestine associated with high mortality and morbidity, mainly due to complications following surgery and loss of functional bowel segment. We describe a preterm neonate presenting on day of life (DOI) 1 with abdominal distension and bilious vomiting, who was operated on DOI 2. No resection of bowel segment was performed; side to side anastomosis done. Post-operatively, the neonate was started on enteral feeds on DOI 10, tolerated well, and was discharged on DOI 18 in a stable condition.